A role of microflora in influence of periodontium disease of cats - Портянко, Т. В. (Scientific Progress & Innovations, 2012)
The literary over are brought data about influence of microorganisms of dental name-plate on development of illnesses of periodontium. Specific composition of microflora of oral cavity is certain at the used for setting fire diseases of periodontium for domestic cats and comparatively with clinically healthy animals. It is set that a coccal microflora prevails at gingivitises, in particular yellow-green staphylococcus, part of enterobacters increases at parodontium. An investigational sensitiveness of the distinguished microorganisms to the antibiotics and these recommendations are to their application.